Natural proxy records of temperature- and hydroclimate variability with annual resolution from the Northern Balkan–Carpathian region for the past millennium – Review & recalibration. (10th September 2016) - Kern, Zoltán; Németh, Alexandra; Horoszné Gulyás, Margit; Popa, Ionel; Levanič, Tom; Hatvani, István Gábor
Abstract: A systematic compilation of temperature (n = 10) and moisture sensitive (n = 4) proxy records of the Northern Balkan–Carpathian (NBC) region with annual resolution for the past millennium is presented and evaluated. The proxy-climate relationship is re-evaluated using a uniform climatological dataset providing a longer calibration. The originally determined response seasons were in the most part verified. Spectral constraints were established by combining wavelet coherence analysis and band filtering, thus, the signal-to-noise ratio was successfully improved in certain cases, either by separating the temperature/moisture sensitive frequencies in complex signals, and/or by extracting "focus" bands. In the case of winter temperature, the earliest available dates in the natural proxy records were 1774 AD, for spring and summer they were 1732 AD and 1040 AD respectively, while for hydroclimate this date was 1497 AD. Although only one record was available for winter, it showed a pronounced similarity to winter temperature reconstructions from adjacent areas outside the NBC. Spring thermal proxies were comprised of grape-vine phenology data from the Western NBC margin, these being in quite good agreement with each other, for instance, in the case of the characteristic mutual decadal pattern the mild springs of the 1750s. In addition, a common long-term cooling trend was observed, starting in the mid-18th century and ending at the turn of the 20th century. The comparison of summer temperature records indicated that proxies of the same origin/source tend to show a stronger mutual variation than those located close to each other, but of different types. This serves as a warning in the interpretation of climate field reconstructions from multiproxy networks. The studied summer proxies show a remarkably strong linear relationship with nearby records outside the NBC, weakening as their distance increases. The two most persistent multi-decadal cold summer periods (∼1780–1840 & 1430–1500 AD) were decisively mirrored in the proxies. The longest and most recent reconstruction from the North Slovakian Tatras shows a unique warming (after ∼1900 AD) reflected neither within, nor outside the NBC, casting doubt on its reliability. In general, weaker coherence was observed between the hydroclimate proxies, drawing attention to a general phenomenon: the range of the spatial representativity of hydroclimate proxies is usually smaller. Therefore, their network should be further developed. One of a few shared regional summer drought periods occurred in the 1750s, being most pronounced in the Central and Southeastern NBC. Moreover, this was reflected in the neighboring South Moravian drought history, too. These results will hopefully serve as a stepping-stone for future research on spatiotemporal patterns of climate changes and their causes in the NBC region.